2010
DOI: 10.1017/s1047951109990503
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial perfusion magnetic resonance imaging for detecting coronary function anomalies in asymptomatic paediatric patients with a previous arterial switch operation for the transposition of great arteries

Abstract: Magnetic resonance imaging evaluation of myocardial perfusion and viability is feasible in paediatric patients long after arterial switch operation. No signs of myocardial ischaemia or necrosis were documented in this young asymptomatic population. Further studies including coronary angiography correlation are needed to validate magnetic resonance imaging results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 45 publications
(70 reference statements)
0
23
1
Order By: Relevance
“…With such low prevalence, it is not surprising that previous small studies often did not identify evidence of myocardial ischemia. 6,22,30 Furthermore, we found no significant difference between those with and those without LGE with regard to symptoms.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…With such low prevalence, it is not surprising that previous small studies often did not identify evidence of myocardial ischemia. 6,22,30 Furthermore, we found no significant difference between those with and those without LGE with regard to symptoms.…”
Section: Discussioncontrasting
confidence: 65%
“…7 However, despite its established role in congenital cardiac practice, the literature on CMR after the ASO comprises only small case series. 6,21,22 The present study is the first to characterize the range of biventricular size and function, great vessel dimensions, semilunar valve function, and myocardial viability in a large cohort of mostly asymptomatic adolescents and young adult patients followed in a single center in which CMR has been used routinely in this patient group starting in the second decade of life. 23 The reference data presented here can be used to determine how individual patients compare with their peers.…”
Section: Discussionmentioning
confidence: 98%
“…In two reports describing a total of 55 asymptomatic ASO patients who underwent stress perfusion CMR, no defects at stress were detected. 109,110 The LGE technique has identified prior myocardial infarction in only a small proportion of patients after ASO. 73,109,110 Thus, on the basis of these studies, both CMR stress imaging and LGE appear to have a low positive yield in asymptomatic ASO patients.…”
Section: Postoperative Assessment Of Tga With Cmrmentioning
confidence: 99%
“…109,110 The LGE technique has identified prior myocardial infarction in only a small proportion of patients after ASO. 73,109,110 Thus, on the basis of these studies, both CMR stress imaging and LGE appear to have a low positive yield in asymptomatic ASO patients. Larger studies that include symptomatic patients and have longer term follow-up are needed to better define the indications and prognostic value of these CMR techniques.…”
Section: Postoperative Assessment Of Tga With Cmrmentioning
confidence: 99%
“…Moreover, late gadolinium enhancement may be combined with stress perfusion MR to detect coronary involvement after the ASO in one comprehensive protocol, although the yield seems to be low for detecting myocardial ischemia, and it has been suggested that cardiac MR imaging is not indicated routinely to evaluate possible myocardial ischemic damage in asymptomatic and clinically stable adult patients after the ASO. 7,8 Other vascular sequelae after ASO involve the neopulmonary root and pulmonary artery branches. Pulmonary branch stenosis is seen in two third of patients after the ASO and is the most common reason for reintervention.…”
Section: See Article By Shepard Et Almentioning
confidence: 99%